A factorial survey on the justice of earnings within the SOEP-pretest 2008 - Carsten Sauer; Stefan Liebig; Katrin Auspurg; Thomas Hinz; Andy Donaubauer (Institute for the Study of Labor (IZA), 2009)
In the 2008 Socio-Economic Panel Study (SOEP) Pretest, the factorial survey method was tested for the first time for use in the SOEP longitudinal study. In this paper, we describe the construction and application of the vignette module, which has its origins in the field of justice research and is used in particular in the measurement of income justice. We show that the factorial survey method is applicable in large-scale survey research when taking certain constraints into account, and that respondents of varying ages and educational groups are able to deal sufficiently well with answering the questions. The results obtained suggest that older respondents tend to take fewer dimensions into consideration in forming their opinions. Further studies will be needed to determine whether this is evidence that the evaluation tasks were too complex for these respondents and should thus be interpreted as a method effect, or whether it represents a valid substantive result. The results of the study demonstrate convincingly that alongside occupation, education, and performance - factors relating directly to employment - familial aspects such as civil status, the partner's employment status, and number of children constitute important criteria for determining what constitutes a fair income. The factor survey in the 2008 SOEP Pretest offers diverse analytical potential, both from a methodological point of view and in terms of the empirical results obtained. The positive experience with the 2008 SOEP Pretest suggests that the SOEP vignette module can be used effectively in a future wave of the main SOEP survey.
Keywords: C81; D63; J31; 330; Income; justice theory; fairness; factorial survey method; SOEP; Verteilungsgerechtigkeit; Meinung; Meinungsforschung; Faktorenanalyse; Panel; Deutschland